2018
DOI: 10.3390/nu10020165
|View full text |Cite
|
Sign up to set email alerts
|

Guarana (Paullinia cupana) Stimulates Mitochondrial Biogenesis in Mice Fed High-Fat Diet

Abstract: The aim of this study was to evaluate the effects of guarana on mitochondrial biogenesis in a high-fat diet (HFD)-fed mice. C57BL6J mice were divided in two groups: high-fat diet HFD and high-fat diet + guarana (HFD-GUA). Both groups received HFD and water ad libitum and the HFD-GUA group also received a daily gavage of guarana (1 g/kg weight). Body weight and food intake was measured weekly. Glycemic, triglyceride, and cholesterol levels were determined. VO2 and energy expenditure (EE) were determined by indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…In a double blind RCT clinical trial enrolling 364 cancer patients, treatment with Panax quinquefolius led to a significant improvement in fatigue symptoms [ 240 ]. In various pre-clinical models, plant species demonstrated a number of activities, such as reduced mitochondrial dysfunction with Boerhavia diffusa [ 241 ], restored mitochondrial integrity with Hippophae rhamnoides [ 242 ] and increased mitochondrial biogenesis with Paullinia cupana [ 243 ]. A molecular mechanism for mitochondrial biogenesis was demonstrated in mouse muscle cells treated with Cinnamomum cassia, which stimulated energy expenditure via upregulation of mitochondrial biogenesis factors such as PGC1αα, NRF-1, and Tfam [ 244 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a double blind RCT clinical trial enrolling 364 cancer patients, treatment with Panax quinquefolius led to a significant improvement in fatigue symptoms [ 240 ]. In various pre-clinical models, plant species demonstrated a number of activities, such as reduced mitochondrial dysfunction with Boerhavia diffusa [ 241 ], restored mitochondrial integrity with Hippophae rhamnoides [ 242 ] and increased mitochondrial biogenesis with Paullinia cupana [ 243 ]. A molecular mechanism for mitochondrial biogenesis was demonstrated in mouse muscle cells treated with Cinnamomum cassia, which stimulated energy expenditure via upregulation of mitochondrial biogenesis factors such as PGC1αα, NRF-1, and Tfam [ 244 ].…”
Section: Resultsmentioning
confidence: 99%
“…From this study the 34 plant species with a documented AChEI activity are thus of prospective interest (Table 7; Additional file 4: Table S4). Reduced mitochondrial dysfunction In vivo mouse/rat Citrus paradisi [245] Matricaria chamomilla [246] Vitis vinifera [247] Rat cell line Boerhavia diffusa [241] Maintained/ restored mitochondrial integrity Rat glial cells Hippophae rhamnoides [242] Rat neuron Solanum indicum [248] Mitochondrial biogenesis upregulation In vivo mouse Paullinia cupana [243] Theobroma cacao [249] Mouse muscle cells Cinnamomum cassia [244] Improved mitochondrial energy metabolism Rat brain mitochondria Carthamus tinctorius [250] Reduced fatigue Clinical trial Panax quinquefolius [240] Tyler and Tyler Natural Products and Bioprospecting (2022) 12:34 For instance, AChE inhibition was associated with improved memory and/or cognition in rodent studies with extracts from Carthamus tinctorius [281], Evolvulus alsinoides [282] and Xylia xylocarpa [285]. In an in vitro and rat brain cell study, sarsasapogenin (Table 3) (from Asparagus racemosus) demonstrated AChE inhibition, anti-amyloidogenic activity, anti-oxidant and neuroprotective effects, suggesting a multi target directed ligand potential of sarsasapogenin for AD therapy [50].…”
Section: The Cholinergic Hypothesismentioning
confidence: 99%
“…Os primeiros estudos com guaraná foram inicialmente conduzidos com vistas a melhorias do desempenho atletas. Contudo, o guaraná passou a ser mais consumido como um dos componentes de bebidas energéticas usadas pelos consumidores para perda de peso (LIMA et al, 2018). Campanhas publicitárias com frases que sugerem queima de calorias e estímulos no metabolismo deixam implícitos os conceitos consumo para perda de peso (BALLARD et al, 2010).…”
Section: Aplicações Práticasunclassified
“…(2019) reported that guarana seed powder supplementation (0.5% [w/w] of total diet) in male Wistar rats for 18 weeks prevented weight gain, insulin resistance acquisition, and adipokine dysregulation while inducing brown adipose tissue expansion. Moreover, an 8‐week guarana supplementation (1 g/kg) in mice led to an increase in energetic metabolism (energy expenditure) and stimulated mitochondrial biogenesis, contributing to weight and adipose tissue accumulation control, even when associated with a high‐fat diet (Lima et al., 2018).…”
Section: Effects On Human Healthmentioning
confidence: 99%